Hybrid Organic/PbS Quantum Dot Bilayer Photodetector with Low Dark Current and High Detectivity. (17th January 2018) - Wei, Yuanzhi; Ren, Zhenwei; Zhang, Andong; Mao, Peng; Li, Hui; Zhong, Xinhua; Li, Weiwei; Yang, Shiyong; Wang, Jizheng
Abstract: Owing to their ease of fabrication, low cost, and high flexibility, organic materials have attracted great interests in photodetector (PD) applications. However, suffering from large dark current, small photocurrent, low on–off ratio, and low sensitivity, performances of bare organic‐based PDs are not satisfactory. Integrating organic materials with other novel semiconductor materials offers an opportunity to overcome these drawbacks. Here, a lateral hybrid organic/lead sulfide (PbS) quantum dot bilayer PD is designed and fabricated, which significantly suppresses the dark current and enhances the photocurrent, leading to improved light detecting capability. Meanwhile, the bilayer PD can be made on a flexible polyimide substrate. Abstract : A hybrid organic/PbS quantum dot bilayer photodetector is designed and fabricated. Compared with bare organic and bare PbS devices, the bilayer device exhibits significantly improved performance in responsivity, detectivity, signal‐to‐noise ratio, and linear dynamic range. The device also shows potential in future flexible optoelectronics.